2012
DOI: 10.1038/oby.2012.40
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term High Fat Feeding Increases Organ Injury and Mortality After Polymicrobial Sepsis

Abstract: The purpose of this study was to examine the effect of short-term high fat feeding on the inflammatory response in polymicrobial sepsis. Male C57BL/6 mice at six-weeks of age were randomized to a high-fat diet (HFD) (60% kcal fat) or control diet (CD) (16% kcal fat) for 3 weeks. After 3 weeks of feeding, sepsis was induced by cecal ligation and puncture (CLP) and animals were monitored for survival. In a separate experiment, after 3 weeks of feeding mice underwent CLP and were sacrificed at various time-points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 42 publications
9
40
1
1
Order By: Relevance
“…This is because LDLr 2/2 mice gain less weight and fat mass when fed a WHF diet compared with LDLr +/+ mice on the same background and are thus less prone to obesity and obesity-induced inflammation (45)(46)(47). Of interest, an acute dietary intervention of 1 wk did not alter the T cell response in CHS, likely because the lipid composition of T cells had not changed after 1 wk of WHF diet and/or owing to enhanced (polarized) innate inflammatory responses to the acute high-fat feeding (48), at the expense of a lower T cell response. LDLr 2/2 mice do not possess LDL receptors, and therefore liver and other cell types cannot remove cholesterol-rich intermediatedensity lipoproteins and LDLs from plasma, resulting in the buildup of circulating lipids (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…This is because LDLr 2/2 mice gain less weight and fat mass when fed a WHF diet compared with LDLr +/+ mice on the same background and are thus less prone to obesity and obesity-induced inflammation (45)(46)(47). Of interest, an acute dietary intervention of 1 wk did not alter the T cell response in CHS, likely because the lipid composition of T cells had not changed after 1 wk of WHF diet and/or owing to enhanced (polarized) innate inflammatory responses to the acute high-fat feeding (48), at the expense of a lower T cell response. LDLr 2/2 mice do not possess LDL receptors, and therefore liver and other cell types cannot remove cholesterol-rich intermediatedensity lipoproteins and LDLs from plasma, resulting in the buildup of circulating lipids (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that APN plays pivotal roles in the regulation of acute inflammatory responses [8][9][10][11][12][13][14][15][16][17], the changes in the expression levels of endogenous APN and AdipoR during such conditions have not been fully elucidated, especially in females. Therefore, the present study mainly focused on the effects of LPS-induced sepsis on APN and AdipoR expression in peripheral and central tissues in female rats.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have detected alterations in endogenous APN and AdipoR expression levels under septic conditions, the results of these studies are contradictory. For example, whilst some reports have shown that serum APN levels are decreased by LPS-or cecal ligation and puncture (CLP)-induced sepsis in WT mice and rats [10,11,18], another study found that the serum APN level was not affected by CLP-induced sepsis in WT mice [12]. In addition, the injection of a septic dose of LPS into lean male rats did not affect their visceral WAT APN mRNA expression.…”
Section: Effects Of Lps Injection On the Circulating Levels Of Adiponmentioning
confidence: 99%
See 1 more Smart Citation
“…98,99 However, there is cumulative evidence that obese patients are more prone to having severe complications from common infections. 100,101 In an experimental cecal ligation and puncture (CLP) model of sepsis in mice, diet was modified briefly to induce obesity and assess inflammatory response. The model demonstrated that mice had a lower chance of survival and greater organ damage, which was dependent on changes in nuclear factor-κB.…”
Section: Sepsis In Obese Patientsmentioning
confidence: 99%